The lifeguards eaudiobook A novel. - Eyre Ward, Amanda (Random House Audio, 2022)
“A book that is at once riveting and relevant as it unpeels the various meanings of motherhood, family, and loyalty. I tore through it.”—Miranda Cowley Heller, author of The Paper Palace   The bonds between three picture-perfect—but viciously protective—mothers and their close-knit sons are tested during one unforgettable summer in a gripping novel from the New York Times bestselling author of The Jetsetters . Austin’s Zilker Park neighborhood is a wonderland of greenbelt trails, live music, and moms who drink a few too many margaritas. Whitney, Annette, and Liza have grown thick as thieves as they have raised their children together for fifteen years, believing that they can shelter them their children from an increasingly dangerous world. Their friendship is unbreakable—as safe as the neighborhood where they've raised their sweet little boys. Or so they think.  One night, the three women have been enjoying happy hour when their boys, lifeguards for the summer, come back on bicycles from a late-night dip in their favorite swimming hole. The boys share a secret—news that will shatter the perfect world their mothers have so painstakingly created.     Combining three mothers’ points of view in a powerful narrative tale with commentary from entertaining neighborhood listservs, secret text messages, and police reports, The Lifeguards is both a story about the secrets we tell to protect the ones we love and a riveting novel of suspense filled with half-truths and betrayals, fierce love and complicated friendships, and the loss of innocence on one hot summer night.